The Use of Game-Based Learning Media to Support Students’ Cognitive Abilities in Mathematics - Khoirunnisya, Melati; Anwar, Lathiful; Kusumasari, Vita (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Cognitive abilities are very important for students to have because they are related to the thinking process. However, students' cognitive abilities in Indonesia are relatively low, so efforts are needed to develop students' cognitive abilities. Currently, games have become a popular activity for children. Games designed specifically for learning mathematics have the potential to help students understand abstract mathematical material. The purpose of this study is to conduct a literature review on the use of games-based learning media to support students' cognitive abilities in mathematics learning. The research method used is a systematic literature review. The stages are research question, data selection and extraction, and data analysis. Data was obtained by collecting all articles related to the research topic. Articles are taken from Google Scholar and Springer Link databases. From a total of 1836 articles obtained from the two databases, 15 articles were selected based on quality assessment criteria for analysis. The results of the research are that the use of games-based learning media in mathematics learning has various positive impacts on students' cognitive abilities. Games-based learning media can improve numeracy skills, mathematical communication, mathematical representation, and higher-level thinking. This research can become literature for researchers who will develop games-based learning to support students' cognitive abilities.